1989
DOI: 10.1038/sc.1989.19
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid paraplegic locomotion with the ParaWalker using intramuscular stimulation: a single subject study

Abstract: SummaryFunctional intramuscular electrical stimulation of the gluteus maximus and gluteus medius on the stance side whilst walking is reported. The subject was an adult, male, post-traumatic complete paraplegic with lesion level at Tl. He had been using surface stimulation to aid his walking with the adult Para Walker Orthosis but suffered unpleasant anterior abdominal wall muscle contractions with high amplitude stimula tion. The experimental use of percutaneous intramuscular Platinum/Iridium wire electrodes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…A 4-month training protocol including preparatory ambulation, LE FES, and combined FES-RGO utilization significantly reduced energy expenditure for walking, but appeared impractical for community mobility [90]. Nene and Jennings added intramuscular glutei FES to the hip guidance orthosis (HGO) or parawalker and produced modest benefits in increased speed of ambulating with crutches, but found many of the same limitations that were experienced with the FES-RGO system, i.e., slow walking, difficult donning, difficult transfers, and less than desirable aesthetics [93]. Comparison of the commercially available advanced reciprocal gait orthosis (AR-GO) with and without FES and Parastep have demon-strated the latter to be more user-friendly (see Fig.…”
Section: Lower Extremitymentioning
confidence: 99%
“…A 4-month training protocol including preparatory ambulation, LE FES, and combined FES-RGO utilization significantly reduced energy expenditure for walking, but appeared impractical for community mobility [90]. Nene and Jennings added intramuscular glutei FES to the hip guidance orthosis (HGO) or parawalker and produced modest benefits in increased speed of ambulating with crutches, but found many of the same limitations that were experienced with the FES-RGO system, i.e., slow walking, difficult donning, difficult transfers, and less than desirable aesthetics [93]. Comparison of the commercially available advanced reciprocal gait orthosis (AR-GO) with and without FES and Parastep have demon-strated the latter to be more user-friendly (see Fig.…”
Section: Lower Extremitymentioning
confidence: 99%
“…Several studies have shown improved gait speeds and lower energy consumption when FES and the RGO are combined (Solomonow et al, 1989, 1997; Hirokawa et al, 1990; Petrofsky and Smith, 1991; Isakov et al, 1992). Others have combined stimulation with the HGO (McClelland et al, 1987; Nene and Jennings, 1989); the Hybrid Assistive System (Popovic et al, 1989, 1990; Popovic, 1990), the Case Western Hybrid System (Ferguson et al, 1999; Marsolais et al, 2000), the Strathclyde Hybrid System) (Yang et al, 1997; Greene and Granat, 2003), and the Controlled-Brake Orthosis (Goldfarb and Durfee, 1996; Goldfarb et al, 2003). …”
Section: Orthoticsmentioning
confidence: 99%
“…It is then free to swing with the momentum of the previous step. Crutches are used to advance the trunk over the stance leg (48). This device has also been used clinically as a purely mechanical orthosis, with success especially among children (19).…”
Section: Fns/orthotic Hybrid Systems For Paraplegic Walkingmentioning
confidence: 99%